Corruption & Purity - Rose-Ackerman, Susan (Daedalus, 2018)
Corruption is a complex and contested concept that raises difficult ethical and legal issues at the borderline between individuals’ public and private roles. What is appropriate or required in one role may be inappropriate or even illegal in another. Based on these concepts of role and responsibility, I begin this essay by analyzing three cases that fit comfortably into the “illegal corruption” category: so-called grand and petty corruption and electoral fraud. These categories express widely accepted boundaries at the interface between public power and private wealth. I then discuss more ambiguous cases, such as lobbying and campaign finance, that demand nuanced legal and policy solutions. Responses to both types of behavior must go beyond law enforcement to include the reorganization of government institutions and their relationship to the private sector.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2Mi9kYWVkX2FfMDA1MDU